Efek Carbon Emission Disclosure dan Green Intellectual Capital Terhadap Nilai Perusahaan dengan Moderasi Environmental Performance - Putri, Jersy Eprina; Rosia, Rina (AKTSAR: Jurnal Akuntansi Syariah, 2025)
This research aims to determine and analyze the influence of carbon emission disclosure and green intellectual capital on company value with environmental performance as a moderating variable. This type of research is quantitative research that uses secondary data in the form of panel data. The population in this study is energy sector companies registered with ISSI in 2019-2013. The data collection technique used a purposive sampling technique, using several sample criteria, resulting in 7 companies as the research sampl. The data analysis method uses panel data regression techniques with Eviews 12 software. The results of this research are that carbon emission disclosure has a negative and insignificant effect and green intellectual capital has a positive and significant effect. The environmental performance variable is unable to moderate the influence of carbon emission disclosure and green intellectual capital on company value.